Effects of Berberine Plus Inulin on Diabetes Care in Patients With Latent Autoimmune Diabetes in Adults: Protocol for a Randomized Controlled Trial - Zhang, Rong; Xiao, Yang; Yan, Jianru; Yang, Wen; Wu, Xiaomei; Mei, Zubing; Zhou, Zhiguang (Frontiers in Endocrinology, 2022)
Background Latent autoimmune diabetes in adults (LADA) is a heterogeneous form of diabetes, characterized by autoimmune destruction of pancreatic β-cells as well as insulin resistance and is triggered by environmental factors in the context of genetic susceptibility. Berberine (BBR), a small alkaloid isolated from medicinal plants, has antidiabetic, anti-inflammatory, and antibacterial effects. Inulin is a common prebiotic that has been shown to improve glycemic control, alter the gut microbiota and suppress inflammation. The primary purpose of this study was to evaluate the effects of oral BBR and inulin combined with insulin therapy on diabetes care in patients with LADA. Methods and Analysis We will conduct a single-center, prospective, randomized, double-blind, placebo-controlled trial. A total of 240 patients with LADA who have started insulin therapy will be randomly allocated either to the intervention or control group. After a 1-week run-in period, they will complete a 3-month treatment of BBR alone, inulin plus BBR, inulin alone, or placebo. Anthropometric and clinical data will be collected at five time points: baseline, 3 months, 6 months, 9 months, and 12 months from baseline. The primary outcome was the change in glycated hemoglobin levels. Dynamic blood glucose parameters, β-cell function, and gut microbiota, as well as adverse events and quality of life will be monitored. Discussion Glycemic control is critical for preventing the progression of diabetes. Although insulin is a recommended treatment for patients with LADA, there are currently no drugs that can effectively prevent the progressive destruction of pancreatic β-cells or maintain their function. Several studies have found that when berberine and prebiotics are used alone, they have beneficial metabolic effects. This clinical research protocol will assess the efficacy of the combined treatment of berberine plus inulin and provide new ideas for future pharmacological research and clinical practices in diabetes care and glycemic control for LADA patients. Ethics and Dissemination This study has been approved by the Ethics Committee of National Clinical Research Center of the Second Xiangya Hospital of Central South University (approval number: 2021–046). Clinical Trial Registration ClinicalTrials.gov, identifier NCT04698330